HES6 drives a critical AR transcriptional programme to induce castration‐resistant prostate cancer through activation of an E2F1‐mediated cell cycle network - Ramos-Montoya, A; Lamb, A; Russell, R; Carroll, T; Jurmeister, S; Galeano-Dalmau, N; Massie, C; Boren, J; Bon, H; Theodorou, V; Vias, M; Shaw, G; et al. (EMBO Press, 2014)
Castrate‐resistant prostate cancer (CRPC) is poorly characterized and heterogeneous and while the androgen receptor (AR) is of singular importance, other factors such as c‐Myc and the E2F family also play a role in later stage disease. HES6 is a transcription co‐factor associated with stem cell characteristics in neural tissue. Here we show that HES6 is up‐regulated in aggressive human prostate cancer and drives castration‐resistant tumour growth in the absence of ligand binding by enhancing the transcriptional activity of the AR, which is preferentially directed to a regulatory network enriched for transcription factors such as E2F1. In the clinical setting, we have uncovered a HES6‐associated signature that predicts poor outcome in prostate cancer, which can be pharmacologically targeted by inhibition of PLK1 with restoration of sensitivity to castration. We have therefore shown for the first time the critical role of HES6 in the development of CRPC and identified its potential in patient‐specific therapeutic strategies.